Modelling effects of consumer animosity: Consumers' willingness to buy foreign and hybrid products. (May 2016) - Cheah, Isaac; Phau, Ian; Kea, Garick; Huang, Yu An
Abstract: This study aims to examine the effects of animosity on consumers' willingness to buy hybrid products i.e. products that involve affiliations of two or more countries (such as branded in Japan but made in China). While consumers' reluctance to purchase foreign products from countries that they have animosity towards is clearly evident in the current literature, little is known about consumers' attitudes towards hybrid products. As such, the study introduces this new construct (i.e. willingness to buy hybrid products) to the animosity model to determine if animositic consumers would be more receptive or willing to accept hybrid products where the animistic tendencies towards foreign countries in question can be negated by the products' domestic affiliations. To conduct this investigation, the study is undertaken in China where the Chinese consumers' animosity towards the Japanese was examined. The data with a usable sample size of 435 were collected in the Chinese city of Nanjing. The findings of the study revealed that the high level of animosity present against the Japanese resulted in the Chinese consumers' unwillingness to buy Japanese products. More importantly, results showed that the Chinese consumers are not any more receptive to hybrid products as such domestic affiliations have not diluted the animosity. Consistent with the literature, the study has also validated that Consumer Animosity to be a higher-order construct indicated by war and economic animosity. Under the conditions of extreme animosity, Consumer Ethnocentrism does not take a significant role in influencing other constructs in the animosity model. Highlights: This study introduces a new construct, Willingness to Buy Hybrid Products to the animosity model. It has also validated that Consumer Animosity to be a higher-order construct indicated by war and economic animosity. It showed evidence that under extreme conditions of extreme animosity, Consumer Ethnocentrism does not influence other constructs in the Model.